Assessing the Impact of the AKFTA on Indonesia-South Korea Trade Flows: A Panel Data Analysis - Fitrianto, Achmad Room; Ramadhani, Rina (Buletin Ilmiah Litbang Perdagangan, 2024)
This study examines the impact of the ASEAN-Korea Free Trade Area (AKFTA) on trade flows between Indonesia and South Korea. This cooperation will impact trade diversion or even trade creation between Indonesia and countries in ASEAN-Korea. This study uses panel data regression analysis and secondary data sources on trade and other macroeconomics from various trusted institutions, such as United Nations, World Bank, etc., as well as the results of scientific research. The research results show that the implementation of AKFTA causes trade diversion on the export side and trade creation on the import side. The findings of this study also highlight that the implementation of AKFTA has an impact on the tendency to increase the value of Indonesian imports from both AKFTA members and non-members. However, the aggregate effect of AKFTA on trade creation is still more significant than trade diversion. Therefore, to overcome the trade diversion resulting from AKFTA, the government can make various efforts by negotiating with trading partner countries to obtain tariff reductions and open market access to new products.